1997
DOI: 10.1002/ana.410410614
|View full text |Cite
|
Sign up to set email alerts
|

A mismatch between kinesthetic and visual perception in Parkinson's disease

Abstract: Kinesthesia may be defective in patients with Parkinson's disease (PD), and this defect conceivably has a role in parkinsonian hypokinetic symptoms. In the present study, PD patients used kinesthetic perception to estimate the amplitude of passive angular displacements of the index finger about the metacarpophalangeal joint and to scale them as a percentage of a reference stimulus. The reference stimulus was either a standard kinesthetic stimulus preceding each test stimulus (task K) or a visual representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(110 citation statements)
references
References 23 publications
(8 reference statements)
3
102
1
4
Order By: Relevance
“…Numerous research findings suggest that a major source of the motor problems in PD is a dysfunctional sensorimotor integration. For example, the performance in tasks that rely on the integration of visual and proprioceptive stimuli are often impaired in PD patients [1,6]. This is consistent with results from animal studies that demonstrated that the basal ganglia respond to somatosensory, auditory and visual inputs with many neurons showing multimodal convergence [12].…”
Section: Discussionsupporting
confidence: 76%
“…Numerous research findings suggest that a major source of the motor problems in PD is a dysfunctional sensorimotor integration. For example, the performance in tasks that rely on the integration of visual and proprioceptive stimuli are often impaired in PD patients [1,6]. This is consistent with results from animal studies that demonstrated that the basal ganglia respond to somatosensory, auditory and visual inputs with many neurons showing multimodal convergence [12].…”
Section: Discussionsupporting
confidence: 76%
“…[1][2][3][4][5] Our results show a dysfunction in the treatment of proprioceptive information by the neurons of the SMA in the parkinsonian situation, which apparently are linked more to a surfeit of inappropriate information than to a decrease in the quantity of information received. Cortical neurons may receive inputs of a misleading complexity or themselves may be incapable of efficiently treating the information they receive.…”
Section: Discussionmentioning
confidence: 81%
“…The amplified motor responses to visual inputs in most of these studies parallel those in our task. It has been suggested that over-weighting of visual information might be a learned response to poor kinaesthetic feedback (Azulay, 2006, Demirci et al, 1997. Poliakoff et al (2007) found a speeding effect for action-relevant visual information in HC but not PD participants.…”
Section: Visual Control Of Walking In Pdmentioning
confidence: 99%